Aspectos idiomáticos em peças brasileiras para violino: de Leopoldo Miguez (1884) a Estércio Marquez (2000) - Pontes, Luciano Ferreira (2012)
This research discuss about idiomatic aspects on Brazilian pieces for the violin written about the end of the XIX century and the beginning of the XX century, which entails pieces written since Leopoldo Miguez (1889) until Estércio Marquez (2000). Through it we tried both to observe and describe the presence of the violin in the panorama of the Brazilian music under the perspective of the circularity, appraising critically the hybrid cultural process that permeates the musical production in Brazil. For this study some facts were considered such as social, cultural and aesthetics related to the selected works. Based on the observation, comparisons and musical analysis focused on the diversity of the aspects of the instrument it was possible to recognize and describe some tendencies important to the compositional handwriting for the violin in Brazil. The bibliography review contextualizes the violin in the Brazilian musical panorama of the colonial period until the beginning of the XXI century. The second part reveals a data collection about the presence of the violin in Brazil, with focus on the romantic period, the nationalism and pos-nationalism until the uncommon sonorities detected after 1960. The third part contains examples of countless characteristics written or not by European composers, revealing the writings representative of the violin since the romantic period in Brazil nowadays. The conclusion points to the presence of the violin permeating the panorama of the Brazilian music with notable European influence in the compositional treatment, especially through the particularities of the French-Belgium School. A great numbers of works were verified, not only in quantity, but also in diversity, composed during the XX century, and despite the nationalistic production also have had presented idiomatic aspects originated from the European, they were identified as having some new bow-strikes considered typically from Brazil, which produces a sound in a different manner in relation to the traditional ones.